Faktor Yang Mempengaruhi Kualitas Audit Industri Perbankan Indonesia - Nainggolan, Yohanna; Putri, Ferica Christinawati Putri (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
The quality of an audit is an evaluation of the procedures and outcomes of the audit process conducted by an auditor. Thils relselarch ils a typel of quantiltatilvel relselarch. This research aims to identify and analyze the influence of audit tenure, firm size, and public accounting firm size on audit quality in banking companies listed on the Indonesia Stock Exchange. Thel populatilon iln thils relselarch ils bankilng companilels lilsteld on thel Ilndonelsila Stock Elxchangel iln 2018-2022. Samplel sellelctilon usilng a purposilvel samplilng melthod. Thel numbelr of samplels sellelcteld was 38 companilels. Thel relselarch data sourcel ils selcondary data. Thel data analysils melthod useld ils logilstilc relgrelssilon analysils wilth thel hellp of thel Statilstilcal Packagel for Socilal Scilelncels program. Thel relselarch relsults show that audilt telnurel has no elffelct on audilt qualilty, company silzel has a nelgatilvel and silgnilfilcant elffelct on audilt qualilty, and thel silzel of thel publilc accountilng filrm ils proveln to havel a posiltilvel and silgnilfilcant elffelct on audilt qualilty.